Representasi Maskulinitas pada Tokoh Gay Sarawat dalam Serial Film 2gether: The Series - Pramitha, Ni Kadek Ratri; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium, 2022)
The concepts of sex and gender have different understandings. However,  the existing social construction emphasizes that the ideal gender behavior is in  accordance with sex identity, namely that men must be masculine and women  must be feminine and must like the opposite sex. Various stereotypes then  emerged for homosexuals, one of it was gay who did not have masculinity. This  study aims to describe the problem through the character of Sarawat in 2gether:  The Series through a qualitative approach. This study uses Roland Barthes' semiotic analysis to examine the meaning of denotation and connotation and  then it will be associated with the myth of masculinity which refers to the  characteristics of masculinity based on David and Brannon with Beynon. The results of this study are in the form of several categories of representation of  masculinity according to David and Brannon with Beynon on the characters of  Sarawat, such as no sissy stuff (not girls), be a big wheel (get admiration from  others), give 'em hell (aggressive and brave), be a sturdy oak (able to hide  emotions), new lad (macho and build a life around football), and metrosexual. In  addition, the character Sarawat is sexually oriented gay king, so it can be said  that this film series tries to provide new knowledge about the various genders that  exist in Thailand.